A Structure of the Cooling System - Vladimir Hlavna; Dusan Sojcak; Dalibor Barta (Communications - Scientific letters of the University of Zilina, 2005)
Some problems related to energetic flows in a cooling system of the combustion engine equipped with a non-conventional cooling circuit are described in this paper. The verification was carried out on a real diesel tractor engine by exploring the thermal balance. Actually, it is an assessment of the influence of alternative cooling liquid on the engine parameters with a particular attention to the flow of after-expansion energy into the cooling system for its further use. Thermal balance is evaluated by means of a reduced output number related to heat or energy chemically bound in fuel, energy led by the cooling system and energy corresponding to the effective output. The value of reduced output number gives attainable utility output per a supply unit of the given equipment (supposing that the energy of the coolant is used for the operation of other equipment, e.g. air-conditioning equipment).The improvement of the output number of the combustion engine as an energetic source can be achieved through the use of exergic part of energy transformed in the combustion engine.